ANALISIS KESALAHAN SISWA BERDASARKAN PROSEDUR NEWMAN DALAM MEMECAHKAN MASALAH MATEMATIS MATERI SISTEM KOORDINAT KARTESIUS - Tiara Aurelly Ferta, - (2023)
ABSTRACT Tiara Aurelly Ferta. (1804241). Analysis of Student Errors based on Newman's Procedure in Solving Mathematical Problems of Cartesian Coordinate System Material. This study was motivated by the number of students making mistakes in solving mathematical problems in the form of story problems, especially in the Cartesian Coordinate System material. It is necessary to analyze the errors made by students in solving mathematical problems in the form of story problems. This study aims to provide an overview or describe the errors made by students in solving mathematical problems in the form of story problems that contain the concept of the Cartesian Coordinate System based on Newman's procedure, knowing the causal factors, along with knowing the solution. This research is qualitative research with a case study research design. The subjects in this study were 8th grade students at one of the public junior high schools in Bandung City. Data collection was done through test instruments, interviews, and literature studies. The results of this study found all types of errors based on Newman's procedure, namely reading, comprehension, transformation, process skill, and encoding. The factors causing the errors are: (1) students did not understand the meaning of keywords; (2) students were not careful and rushed in understanding the problem; (3) students did not know the strategy to solve the problem; (4) students did not know the method of finding solutions; and (5) students forgot and were not used to writing the final answer. The solution that can be done to minimize student errors in solving story problems is to use the Problem-based Learning (PBL) learning model. Keywords: Error Analysis, Mathematical Problem Solving in the Form of Story Problems, Cartesian Coordinate System, Newman-based Errors, Qualitative